Rectal digestibility of nutrients in growing pigs, fed with taro silage (Colocasia esculenta (L.) Schott). Technical note - Caicedo, W.; Rodríguez, R.; Lezcano, P.; Ly, J.; Vargas, J. C.; Uvidia, H.; Samaniego, E.; Valle, S.; Flores, L. (Cuban Journal of Agricultural Science, 2018)
A total of eight castrated male pigs were used, from the Yorkshire x Landrace x Duroc commercial cross, with an average live weight of 36.25 ± 2.12 kg. These animals were distributed at a rate of four pigs in two treatments: T1 control diet (corn and soybeans) and T2 with inclusion of 20% of taro silage with whey and molasses B of sugarcane in the diet. A completely randomized design was applied to determine the rectal digestibility of nutrients from the taro tubers silage (Colocasia esculenta (L.) Schott) in growing pigs. The best coefficients (P <0.05) of rectal digestibility of dry matter (DM 91.20 %), organic matter (OM 93.33 %), crude protein (CP 85.08 %), crude fiber (CF 59.48 %) and digestible energy (DE 89.88 %) were showed by pigs fed 20 % silage in the diet. The rectal digestibility of DM, OM, CP, CF and DE showed high utilization rates, when including 20% taro tubers silage in the diet, which guaranteed a food with optimal nutritional characteristics for growing pigs. Key words: pig feeding, use of nutrients, fermentation, molasses B, whey.